1993
DOI: 10.1096/fasebj.7.13.8405812
|View full text |Cite
|
Sign up to set email alerts
|

Human immune response to polydimethylsiloxane (silicone): screening studies in a breast implant population

Abstract: Although initially it was thought that polydimethylsiloxane (silicone) was biologically inert, recent published studies have demonstrated varying levels of IgG antibody reactive with this structure in humans. The objective of our study was to determine whether silicone implanted in humans results in a measurable immune response directed against a 3700 mol wt hydroxyl terminated silicone molecule and whether that response could be correlated with the level of presumed silicone exposure as inferred by clinical h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(27 citation statements)
references
References 0 publications
0
26
0
1
Order By: Relevance
“…[16] Silicone fluids can also interact with proteins and structurally related polymers. [17] It has been shown that dimethylsilicones are not themselves immunogenic [18] but, when emulsified with immunogenic proteins, lead to higher immune responses. That is, silicones behave as adjuvants.…”
mentioning
confidence: 99%
“…[16] Silicone fluids can also interact with proteins and structurally related polymers. [17] It has been shown that dimethylsilicones are not themselves immunogenic [18] but, when emulsified with immunogenic proteins, lead to higher immune responses. That is, silicones behave as adjuvants.…”
mentioning
confidence: 99%
“…Women having been implanted with silicone breast prostheses have statistically higher levels of anti-silicone IgG [15]. Since 1960, polymethylmethacrylate has been shown to be immunologically inactive as an implant material.…”
Section: Discussionmentioning
confidence: 99%
“…In other studies it has been hypothesised that silicone could induce an autoimmune response. Elevated levels of anticollagen autoantibodies in women with silicone implants were reported [6,7], with the highest being found in women whose implants had ruptured or leaked [20]. Solomon et al [5] evaluated 176 symptomatic patients with silicone breast implants, nearly 50% of whom required explantation because of capsular contracture or rupture.…”
Section: Discussionmentioning
confidence: 99%